A colaboração crítica no desenvolvimento de uma atividade de formação de professores a distância - Oliveira, Wellington de (2009)
The main aim of this study was to discuss the critical collaboration as a category to understand the development of an activity of teachers' formation in virtual context, leaving of the following questions: Is it possible to develop the critical collaboration in virtual context of learning? What operations were developed to solve the conflicts and like them they do signal for critical collaboration in virtual context of learning? The theoretical-methodological bases of the work come from studies of the Theory of the Activity (Leontiev, 1978,1983), that it establishes the activity as a group of actions and operations addressed by reasons, seeking to reach certain goal or I aim at; of the Critical Research of Collaboration (Magalhães, 2004,2007), that it understands educational and researchers as building subjects of the knowledge about the activity of teaching in a critical and collaborative dimension that it is done collective, social and historically, with views the transformation of their actions and practices; and of the discussions about Technological Formation of Teachers (Freire,2008, Kenski, 2005 Lopes,2003). The results show that the experience of applied critical collaboration in virtual context lived by the collaborators opened perspectives to the development of a process virtual pedagogic plural, homelike of the established contradiction in the dialogue among the collaborators as form of moving forward collectively, committed with the transformation in the movement of a historical and social process. The group of the articulations developed in this process revealed that to learn and to teach in virtual context implicates in the action of pedagogic support, developing actions capable to render this support. Sending us to think that the applied critical collaboration in virtual context is constituted as one in the support ways to think the didactic relationships, the transmission, use and articulation of the experience of construction of the knowledge in a virtual pedagogic process that it is in permanent reconstruction